APLIKASI KOMPOS ORGANIK LIMBAH JAMUR DENGAN PENAMBAHAN EM4 UNTUK PERTUMBUHAN TANAMAN TOMAT (Solanum lycopersicum L.) - Baiq Nila Kusumawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
The amount of non-organic fertilizer use that decreases the soil quality and the lack of utilization of organic compost by the community especially the compost of mushroom waste. The purpose of this research is to know how to apply organic compost of mushroom waste with the addition of EM4 for the growth of tomato plant (Solanum lycopersicum L.). Implementation of research in March 2013. Type of this research is experimental research and object in this research is tomato plant growth. The research approach used is quantitative approach. Data collection techniques with observation and documentation. This study used a Single Completely Randomized Design (RAL) consisting of three treatments: K0: uncomposted soil; K1: soil added organic compost of mushroom waste with EM4; K2: the soil added organic compost of mushroom waste with tofu pulp. Each was repeated five times, then analyzed using Analysis of Variance (ANOVA) used F test at 5% significance level and continued with real difference test (BNT 5%). The result of the research in general is seen good application by organic compost of mushroom waste on tomato plant growth seen from parameter of plant height F count (39.242)> F table (3,081), number of leaf F count (11.643)> F table (3.081), width leaf F count (10.943)> F table (3.081), wet weight F count (13,043)> F table (3.081) and dry weight F arithmetic (11.863)> F table (3.081). Seen from the above data can be concluded that the application of organic compost of mushroom waste with the addition of EM4 this role for the growth of tomato plants.